MANAGING CLASSROOM SOCIETY DURING THE COVID-19 OUTBREAK AT HIDAYATULLAH TAHFIDZ GLOBAL ISLAMIC SCHOOLS - Supriyono Supriyono; Devita Sulistiana (Bajang Institute, 2022)
The Covid-19 outbreak has intruded schools to work differently and most concerns raised by the community are the interaction of students and learning entities. This paper is aimed to describe classroom society management during the covid-19 outbreak at Hidayatullah Tahfidz Global Islamic Schools. This study employed a single case study. Interviews, observation, and documentation were applied to reach this purpose. It was found out that. The notions of classroom society in Hidayatullah Tahfidz Global Islamic schools at the levels of Playgroup, Kindergarten, Primary School, and Middle School were patterned into two unique approaches in terms of virtual and social-distancing face to face instructional interactions. The schools shared similar approaches to school society management by planning student-teacher interaction in terms of virtual and offline classes and teachers’ home visits, organizing teachers’ tasks for virtual and off class interaction, conducting interactive relationships in virtual classes which were combined with the home visit and in the social-distancing off class sessions, and evaluate methods of virtual and off class interactions among teachers and parents.